Transformation of Literacy-Based Islamic Education Learning Management Integration in Elementary Schools - Supriadi, Supriadi; Hosaini, Hosaini; Sain, Zohaib Hassan (International Journal of Social Learning (IJSL), 2024)
This research integrates Islamic values with literacy skills so students understand religious knowledge and apply these values in everyday life. This research analyzes literacy-based learning management strategies in Islamic elementary education and identifies supporting and inhibiting factors. This research uses a literature study method to analyze literacy-based learning management in Islamic education at elementary schools. The research results show that literacy-based Islamic education learning management significantly increases students' interest in reading and writing. Islamic-based literacy hones reading and writing skills and helps students internalize Islamic texts' moral and spiritual values. These increased literacy skills strengthen students' abilities to analyze, organize ideas, and apply insights in everyday life. Apart from that, Islamic-based literacy contributes to developing student characteristics such as honesty, responsibility, and empathy.